Clinical Features of Peripheral Neurophaty among Onset Type 2 Diabestes Mellitus: A Michigan Neuropathy Screening Instrument (MNSI) Approach - Pamungkas, Rian Adi; Usman, Andi Mayasari; Chamroonsawasdi, Kanittha (Faculty of Nursing, Universitas Hasanuddin, 2023)
Aims: Neuropathy is one of the complications that can occur in patients with Type 2 Diabetes Mellitus, around 21.3% to 34.5%. Untreated neuropathy can lead to diabetic foot ulcers that can lead to amputation. This can be prevented by conducting early detection using a neuropathy screening instrument. The study aimed to identify neuropathy symptoms through early examination of patients with type 2 diabetes using the Michigan Neuropathy Screening Instrument (MNSI). Method: The descriptive study with a survey was approached in this study. One hundred respondents with type 2 diabetes mellitus were selected using the purposive sampling technique. Results: The results showed that out of 100 patients had clinical symptoms of sensory neuropathy, such as pain and sensitivity disorders in the soles of the feet. In addition, autonomic neuropathy is in the form of cramps in the leg muscles. The level of neuropathy showed that from 100 patients, there were 59 respondents with low risk of neuropathy, 40 respondents with moderate risk, and 1 respondent with severe risk. Conclusion: Patients with Diabetes, primarily Type 2, have various neuropathy symptoms such as impaired nerve function: numbness, burning, and hypersensitivity, which can lead to diabetic foot ulcers. Therefore, early detection of neuropathy prevention is essential.